INNOVATION AND MARKETING FOR CULINARY OF LOCAL BASED FOOD PRODUCT IN IWUL VILLAGE, BOGOR - Setiyo Wibowo, FX; Damanik, Darmawan (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
This study aims to find out local culinary products and their marketing in Iwul Village, Bogor and to innovate and to market local-based culinary products in Iwul Village, Bogor. The method used in this study is Qualitative Descriptive with the analysis unit is a business based on tempeh, tofu and catfish in Iwul Village. The analytical method used is triangulation technique consisting of interviews, observations and secondary data. This research was conducted from Fabruary to July 2019 in Iwul Village, Kec. Parung, Bogor, West Java. The results obtained are 1) local-based culinary products in Iwul Village are tofu, tempeh and fresh catfish, while the marketing carried out still uses a conventional system, where buyers and sellers meet and some have used social media namely whats app and face book; 2) while the innovations carried out are innovating culinary products made from tempeh, tofu and catfish, namely cassava donuts, cassava balls, soybean jelly milk, dragon feet oncom, tempe katsu, tofu pudding and wonton catfish (dimsum), as for marketing is to use Instagram social media and register it on the online store.